Obesity epidemiology : from aetiology to public health - Crawford, David, 1960- (Oxford : Oxford University Press, 2010)
This textbook assists those concerned with understanding prevalence & trends in obesity; its health, social & economic consequences, causes of the obesity epidemic, existing evidence regarding strategies to prevent obesity, & the potential of public health initiatives to impact on the population prevalence of obesity.
Previous ed.: published as Obesity prevention and public health. 2005.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Obesity -- Epidemiology; Obesity -- Prevention; Obesity -- Etiology